2007
DOI: 10.1111/j.1570-7458.2007.00538.x
|View full text |Cite
|
Sign up to set email alerts
|

Aromatherapy on a large scale: exposing entire adult holding rooms to ginger root oil increases the mating competitiveness of sterile males of the Mediterranean fruit fly in field cage trials

Abstract: The sterile insect technique (SIT) is widely used in integrated programs against fruit fly pests, particularly the Mediterranean fruit fly, Ceratitis capitata (Wiedemann) (Diptera: Tephritidae). Unfortunately, the mass‐rearing procedures inherent to the SIT often lead to a reduction in male mating competitiveness. One potential solution involves the pre‐release exposure of males to specific attractants. In particular, male exposure to ginger root oil [Zingiber officinale Roscoe (Zingiberaceae); hereafter GRO] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 24 publications
1
31
0
Order By: Relevance
“…The competitiveness of sterile males, and their ability to mate with wild females, was increased by exposing them to GRO aromatherapy the day before release. These results are in line with the recent published literature on the positive impact of GRO aromatherapy on male sexual performance (Shelly et al. 2004, 2007) and on the lack of negative impact on field survival (Paranhos et al.…”
Section: Discussionsupporting
confidence: 91%
“…The competitiveness of sterile males, and their ability to mate with wild females, was increased by exposing them to GRO aromatherapy the day before release. These results are in line with the recent published literature on the positive impact of GRO aromatherapy on male sexual performance (Shelly et al. 2004, 2007) and on the lack of negative impact on field survival (Paranhos et al.…”
Section: Discussionsupporting
confidence: 91%
“…The amount of GRO used depends on the size of the room and the number of flies to be exposed. As little as 20 ml of GRO has been successfully used to expose up to 10–12 million males overnight in large shipping trailers (∼132 m 3 ) in the California sterile C. capitata preventive release programme (Shelly et al. 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…In females, odor preference may be affected by mating behavior: it has been observed that females are more attracted by the male-produced pheromone than the ripe guava odor during early sexual maturity, but this preference is inverted after mating (Jang 1995). Furthermore, the exposure to some natural and synthetic compounds may influence the mating behavior in medfly males (Shelly et al 1996(Shelly et al , 2004(Shelly et al , 2007(Shelly et al , 2008.…”
Section: Introductionmentioning
confidence: 99%